Upgrading Japan's Innovation System to Sustain Economic Growth - Jones, Randall S.. (OECD Economics Department Working Papers, 2006)
Increasing productivity growth through innovation is a key to raising living standards. Although R&D intensity in Japan is the third highest in the OECD area, the benefits do not appear to have been commensurate with the level of investment. The innovation system, which developed during the catchingup process, is largely input-driven and focused on incremental innovation based on closed and stable corporate and employment systems. However, this approach is less appropriate in the current global environment that favours risk-taking and a more open system relying on external linkages. To improve the innovation system, a broad-based strategy is needed, including a reform of framework conditions in the product and labour markets to strengthen competition and mobility, enhance international R&D links and improve the environment for venture business. Education and public research should be upgraded through stronger competition. The effectiveness of science and technology policy should be increased by strengthening its link to economic framework policies. This Working Paper relates to the 2006 OECD Economic Survey of Japan (www.oecd.org/eco/surveys/japan)